Divided Dreamworlds? : The Cultural Cold War in East and West - Segal, Joes; Romijn, Peter; Scott-Smith, Giles, 1968- (Book collections on Project MUSE., 2012)
With its unique focus on how culture contributed to the blurring of ideological boundaries between the East and the West, this important volume offers fascinating insights into the tensions, rivalries and occasional cooperation between the two blocs. Encompassing developments inboth the arts and sciences, the authors analyze focal points, aesthetic preferences and cultural phenomena through topics as wide-ranging as the East- and West German interior design; the Soviet stance on genetics; US cultural diplomacy during and after the Cold War; and the role of popular music as a universal cultural.